Effect Of Occupational Safety And Health On Performance An Empirical Investigation - Dedi Iskamto; Puspa Liza Ghazali; Asraf Afthanorhan; Seflira Narti (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
Employees are important assets of the organization, so many things that need to be considered related to improving performance. An employee's performance will be in accordance with the wishes of the company if the quality of human resources is good. Good performance can also be supported by the presence of occupational safety and health guarantees from the company. The Implementation of the Occupational Safety and Health (OSH) system also influences employee performance. This study aims to determine the effect of Occupational Safety and Health (OSH) on the performance of midwives at the XYZ Islamic Hospital Fetomatenal Installation Riau Province, Indonesia. The results of analyze of primary data using SPSS Version 23, it can be concluded that the work safety variable has a significant effect on performance, knowing that occupational health variables have a significant effect on performance. In addition, it can be concluded that occupational safety and health variables together have a significant influence on performance variables.